The CÃ©lestin Prophecy: Ha Jinâ€™s â€œAfter Cowboy Chicken Came to Town,â€ Lawrence Chuaâ€™s Gold by the Inch, and the Limits of Exoticism - Overaa, East Tennessee State University, USA, Roderick B. (Asiatic: IIUM Journal of English Language and Literature, 2013)
Increasingly, postcolonial scholars are recognising that the discipline must move beyond the mere critique of European imperialism, and that the future lies, in part, in seeking solutions to the conflicts and injustices that remain the persistent legacy of the colonial era. A concurrent trend in literature departments has been the push to incorporate and encourage comparative methodologies. This essay brings into conversation two works of Asian American fiction that address the problematics of transnational encounter in the age of globalisation. In both Ha Jinâ€™s â€œAfter Cowboy Chicken Came to Townâ€ and Lawrence Chuaâ€™s Gold by the Inch the authors explore familiar postcolonial themes: Western economic and cultural hegemony, cultural imperialism, the legacy of the Euro-American colonial era â€“ yet they do so from a very particular (and increasingly common) perspective that as yet has not been sufficiently addressed by postcolonial scholars. Reading these texts through the lens of Roger CÃ©lestinâ€™s theorisation of the limits of traditional literary exoticism in From Cannibals to Radicals, this essay calls for a re-evaluation, not merely of our understanding of literary exoticism, nor merely of our understanding of the transpacific as a political imaginary, but also of our long-held conceptions of national literature and comparative scholarship.